High‐risk human papillomavirus infection clearance following conization among patients with cervical intraepithelial neoplasm grade 3 aged at least 45 years. Issue 1 (24th October 2016) - Zhang, Guorui; Lang, Jinghe; Shen, Keng; Zhu, Lan; Xiang, Yang
Abstract: Objective: To investigate high‐risk human papillomavirus (HPV) infection clearance rates following successful cold knife conization and factors predictive of HPV clearance among patients with cervical intraepithelial neoplasm grade 3. Method: The present retrospective study analyzed clinical data from patients aged at least 45 years with cervical intraepithelial neoplasm grade 3 who had undergone successful cold knife conization and attended regular follow‐up at Peking Union Medical College Hospital, China, between January 1, 2002 and December 31, 2012. HPV clearance rates and potential indicators for HPV clearance were analyzed. Results: Data from 156 patients were included; persistent high‐risk HPV infection was recorded in 78 (50.0%), 45 (28.8%), 35 (22.4%), 24 (15.4%), and 21 (13.5%) patients at 4, 8, 12, 18, and 24 months after conization, respectively. Clearance rates were significantly lower among patients aged at least 55 years compared with younger patients, with increased odds of persistent HPV infection at 8 months (odds ratio [OR] 4.038; 95% confidence interval [CI] 1.766–10.839), 12 months (OR 5.923; 95% CI 2.450–16.604), 18 months (OR 5.957; 95% CI 2.031–17.469), and 24 months (OR 5.327; 95% CI 1.909–17.971) compared with patients aged 45–49 years. Conclusion: Age was a prognostic factor for post‐operative high‐risk HPV infection clearance. Lower clearance rates were observed among patients aged at least 55 years. Abstract : Age was a prognostic factor for post‐operative clearance of human papillomavirus. Human papillomavirus clearance was significantly decreased among patients aged at least 55 years.